2000
DOI: 10.1046/j.1365-2540.2000.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Chilean and Brazilian Alstroemeria species assessed by AFLP analysis

Abstract: One to three accessions of 22 Alstroemeria species, an interspeci®c hybrid (A. aurea´A. inodora), and single accessions of Bomarea salsilla and Leontochir ovallei were evaluated using the AFLPmarker technique to estimate the genetic diversity within the genus Alstroemeria. Three primer combinations generated 716 markers and discriminated all Alstroemeria species. The dendrogram inferred from the AFLP ®ngerprints supported the conjecture of the generic separation of the Chilean and Brazilian Alstroemeria specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…Molecular phylogenetic studies of Alstroemeria were based mainly on Chilean species; only a few Brazilian species were included in these studies (Dubouzet et al, 1998;Han et al, 2000;Aagesen & Sanso, 2003;Aros et al, 2006). These studies, moreover, failed to clearly identify the position and relationships among the studied taxa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular phylogenetic studies of Alstroemeria were based mainly on Chilean species; only a few Brazilian species were included in these studies (Dubouzet et al, 1998;Han et al, 2000;Aagesen & Sanso, 2003;Aros et al, 2006). These studies, moreover, failed to clearly identify the position and relationships among the studied taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Alstroemeria aurea has a wide geographical spread and its ecotypes are believed to be the ancestor of all other Chilean species (Han et al, 2000). Although not found in Brazil, A. aurea plants grow on both sides of the Andean Mountains in Argentina, supporting the possibility that A. aurea ecotypes were also ancestors of the Brazilian species (Han et al, 2000). Based on rbcL data, Aagesen and Sanso (2003, figure 1C) also concluded that A. aurea, among other trans-Andean species, may have shared a common ancestor with the Brazilian species.…”
Section: Taxonomic Significance Of Palynological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the several marker systems, amplified fragment length polymorphism (AFLP; Vos et al, 1995;Lucchini, 2003) is highly reliable for the assessment of genetic variation among and within populations (Folkertsma et al, 1996;Keiper and McConchie, 2000;Loh et al, 2000;Lamote et al, 2002;Curtis and Taylor, 2004). AFLP does not require any prior knowledge of genetic information, an especially useful feature if polymorphic markers are not established in relation to population identity or if sequence information is limited for the species under study (Han et al, 2000;Ajmone-Marsan et al, 2001;De Knijff et al, 2001). Another advantage of AFLP is its capability to produce multilocus fingerprints in a single analysis, significantly reducing the cost of analysis and increasing the possibility of detecting polymorphisms (Vos et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…La clasificación de las especies se basa en características de la inflorescencia, flor, tallo, hojas, frutos y rizomas (Bayer 1987, Han et al 2000, Muñoz & Moreira 2003. Entre las características florales de valor taxonómico previamente consideradas se encuentran el tamaño de las piezas florales, el color de la base de los tépalos internos superiores y sus patrones de dibujos (máculas), la disposición de los tépalos externos, el ápice de los tépalos externos y el tamaño de los tépalos internos superiores respecto de los demás (Muñoz & Moreira 2003).…”
unclassified